Вплив штучного інтелекту на продуктивність праці в різних секторах економіки: український та світовий аспекти - Тополенко, Н. М.; Овсієнко, А. М.; Шеховцова, В. В.; Shekhovtsova, V. V. (Львівський університет бізнесу та права, 2025)
Мета дослідження - аналітична оцінка впливу штучного інтелекту на продуктивність праці в різних секторах економіки України та світу. Узагальнено світові тенденції трансферу технологій ШІ у різних секторах економіки, висвітлено тенденції використання в різних сферах світової економіки та України. Виявлено, високий рівень використання ШІ ‒ це свідчення зворотного характеру впливовості. Доведено стриманий, секторально дроблений ступінь інтеграції штучного інтелекту в українському бізнесі в умовах геополітичних та макроекономічних викликів. Визначено основні завдання використання штучного інтелекту у сфері бізнесу: експеримент; трансфер операційний та кадровий менеджмент, маркетинг та логістика, інтеграція науки та виробництва. Формування національної інноваційно-інвестиційна політика має носити людиноорієнтований характер, а штучний інтелект має виступати лише інструментом людини для підвищення конкурентоспроможності національної економіки.

In the current transformational conditions of the development of the world economy, when geopolitical crises and climate disasters are becoming increasingly acute, the issue of increasing labor productivity through the rational use of innovations, in particular artificial intelligence, is becoming increasingly relevant. The purpose of this study is an analytical assessment of the impact of artificial intelligence on labor productivity in various sectors of the economy of Ukraine and the world. The main research methods: empirical analysis, analysis of development dynamics, index and correlation analysis, scientific abstraction and generalization. The information base for the study was scientific publications of foreign and Ukrainian scientists, official statistical data of the World Bank Group, OECD, Eurostat and the State Statistics Service of Ukraine. According to the results of the study, global trends in the transfer of AI technologies in various sectors of the economy are summarized, and usage trends in various areas of the world economy and Ukraine are highlighted. The TOP-5 Eurozone countries for 2021-2025 are determined. It is established. that a sufficiently high level of AI use does not always correspond to a high level of labor productivity - this is evidence of the inverse nature of influence, and the calculated correlation coefficient confirmed this statement. A restrained, sectorally fragmented degree of integration of artificial intelligence in Ukrainian business was revealed against the background of ongoing geopolitical and macroeconomic challenges. The urgent task of using artificial intelligence in the business sphere was substantiated: research use; constant transfer to operational and personnel management, marketing activities and the logistics sphere; integration of science and production. National innovation and investment policy should be human-oriented, and artificial intelligence should act only as a human tool to increase the competitiveness of the national economy.
The impact of artificial intelligence on labor productivity in various sectors of the economy: Ukrainian and global aspects
Keywords: продуктивність праці; галузі економіки; моделі організації праці; європейська зона; штучний інтелект; економіка та організація інноваційної діяльності; макроекономіка; маркетинг; операційний менеджмент; диджиталізація; трансфер штучного інтелекту; labor productivity; economic sectors; labor organization models; European area; artificial intelligence; economics and organization of innovation activity; macroeconomics; marketing; digitalization; operational management; transfer of artificial intelligence